Ausência da atividade mutagênica de nanotubos de carbono de paredes múltipla, funcionalizados, em células somáticas de Drosophila melanogaster - Machado, Nayane Moreira (2012)
Carbon nanotubes (CNTs) are rigid molecules, flexible and resistant to tensions formed from sheets of carbon (graphene), which at high temperature, ultimately to curl, forming nanometer diameter tubes. Among the different types of CNTs, the multi-walled carbon nanotubes (MWCNTs) can be noted for comprising a set of concentric nanotubes with perfect structures and defect- free materials. Several applications for this material are suggested, including biological applications such as manufacturing of biosensors, backers of drugs and vaccines and other biomaterials. However, before these materials can be incorporated into the market, is necessary to know their cytotoxic and genotoxic effects. Thus, this study aims to evaluate the mutagenicity of carbon nanotubes in somatic cells of Drosophila melanogaster, using the Somatic Mutation and Recombination Test (SMART). For this purpose we have used 72-hour larvae from standard (ST) and high bioactivation (HB) crosses. The larvae from both crosses were treated with solutions containing different concentrations of multi-walled carbon nanotubes (MWCNTs) functionalized (0,50, 100, 150, 200, 250 mμ /mL). For positive control, doxorubicin DXR (0,4 mM) was used, and reverse osmosis water for negative control. The descendants trans-heterozygous (MH) analyzed from both ST and HB crosses, had no significant effect on the frequency of mutant spots when compared with negative control (reverse osmosis water). This way, based on the results and on the experimental conditions mentioned in this study, it can be concluded that MWCNTs were not mutagenic for Drosophila melanosgaster.